The Impact of Higher Education on Leadership Styles in California Local Educational Agencies and How They Affect Turnover Rates and Job Satisfaction in Classified Employment - Babic Tatomirovic, Biljana (Digital Repository of Theses, 2025)
The purpose of this mixed quantitative and qualitative phenomenological study was to explore the employee perception of the impact of the level of education on management styles in California Local Educational Agencies and how those management styles affect their everyday life and job satisfaction. While there is substantial research on the correlation between education and leadership styles, the intersection of higher education, leadership styles and their direct impact on turnover rates and job satisfaction among Classified employees within California Local Educational Agencies remains underexplored. A mixed-method phenomenological approach was employed, combining quantitative surveys, observations, and qualitative interviews. The quantitative component included a survey administered to forty-four Classified employees and managers at the Monterey County Office of Education, focusing on management styles, job satisfaction, managerial performance, and turnover-related factors. Qualitative data were collected through indepth interviews with eight Classified managers and employees selected based on covert observations conducted in public settings, meetings, and daily interactions. Data analysis involved triangulation to identify themes and patterns related to educational attainment and its effect on leadership behaviors. Even though quantitative analysis showed that 51.5% of employees believe that their manager’s level of education impacted their management style, the qualitative analysis and the overall findings indicate that while higher education plays a role in shaping managerial practices, practical experience and interpersonal skills are often seen as equally or even more crucial in effective leadership. Higher education is among the most significant factors in producing management practices within California Local Educational Agencies. Managers with advanced academic qualifications are perceived as better leaders and exhibit management styles that positively impact employee engagement and retention. The practical application of advanced theoretical knowledge remains a key area for improvement. The data suggests customized professional development programs should be implemented to blend academic credentials and real-world management challenges. Advanced education combined with ongoing leadership training should show the best results in improving organizational effectiveness and employee satisfaction.